ANALISIS KEUNTUNGAN PETERNAK SAPI POTONG BERBASIS PETERNAKAN RAKYAT DI KABUPATEN BONE - Asnawi, Hastang, Aslina (Jurnal Ilmu dan Industri Peternakan, 2016)
ABSTRACT. The aims of this research are to analyze of farmers profit in cattle farm based on rural farm. This research was conducted in January to February 2013. Population in this research consists of all of breeders in cattle farm in Bone regency. Location determined based on the number of population of cattle every district, they are big, medium and small population. The sample of breeders selected by random sampling. Collectiong data by observation, interview and using questionaire. Analysis of the data used descriptive statistics analysis. The results showed that average the number of breeding scale is six head. The profit of beef cattle farmers is Rp 2,663,519 per year or Rp 474.291 per year. R/C ratio is 1,11 so this business is feasible. Profit of breeders based on breeding scale was categoried feasible in finansial aspect if the number of breeding scale over fourth head.